Artificial intelligence and journalism: Opportunities, challenges, and ethical considerations for Nepali media - Chaudhary, Bivek (Nepali Media: Issue of Ethics and Sustainability, 2025)
The integration of artificial intelligence (AI) in journalism represents a paradigm shift that is reshaping media landscapes globally, with profound implications for developing nations like Nepal. This comprehensive study examines the multifaceted relationship between AI technology and journalism within the specific context of Nepali media, exploring the opportunities for enhanced news production, distribution, and audience engagement while simultaneously addressing the significant challenges and ethical considerations that arise from this technological transformation. Through a doctrinal methodology encompassing legal, ethical, and technological frameworks, this research investigates how AI applications such as automated content generation, fact-checking systems, personalized news delivery, and data-driven journalism can revolutionize Nepali media practices. The study reveals that while AI offers unprecedented opportunities for improving efficiency, accuracy, and reach in Nepali journalism, it also presents substantial challenges including job displacement concerns, algorithmic bias, misinformation risks, and the need for substantial infrastructure development. The research emphasizes that successful AI integration in Nepali media requires a balanced approach that prioritizes ethical considerations, professional development, and regulatory frameworks while maintaining the core values of journalistic integrity and public service. The findings suggest that Nepali media organizations must adopt a strategic, phased approach to AI implementation, focusing on human-AI collaboration rather than replacement, investing in digital literacy and technical skills, and establishing robust ethical guidelines to ensure responsible AI deployment in journalism.